Post-traumatic stress disorder among recently diagnosed patients with HIV/AIDS in South Africa (2005)
This study examined the prevalence of and factors associated with post-traumatic stress disorder in recently diagnosed HIV/AIDS patients in South Africa. One hundred and forty-nine (44 male, 105 female) recently diagnosed HIV/AIDS patients (mean duration since diagnosis= 5.8 months, = 4.1) were evaluated. Subjects were assessed using the MINI International Neuropsychiatric Interview (MINI), the Carver Brief COPE coping scale and the Sheehan Disability Scale. In addition, previous exposures to trauma and past risk behaviours were assessed. Twenty-two patients (14.8%) met criteria for PTSD. Current psychiatric conditions more likely to be associated with PTSD included major depressive disorder (29% in PTSD patients versus 7% in non-PTSD patients, p= 0.004), suicidality (54% versus 11%, p= 0.001) and social anxiety disorder (40% versus 13%, p= 0.04). Further patients with PTSD reported significantly more work impairment and demonstrated a trend towards higher usage of alcohol as a means of coping. Discriminant function analysis indicated that female gender and a history of sexual violation in the past year were significantly associated with a diagnosis of PTSD. Patients whose PTSD was a direct result of an HIV/AIDS diagnosis (8/22) did not differ from other patients with PTSD on demographic or clinical features. In the South African context, PTSD is not an uncommon disorder in patients with HIV/AIDS. In some cases, PTSD is secondary to the diagnosis of HIV/AIDS but in most cases it is seen after other traumas, with sexual violation and intimate partner violence in women being particularly important.